THE MILLENNIUM DEVELOPMENT GOALS (MDGS) AND GLOBAL POVERTY: HAVE WE REALLY FAILED? - Baidhowah, Adfin Rochmad (Jurnal Politik Pemerintahan Dharma Praja, 2021)
MDGs was implemented over the period 2000-2015 by the United Nations along with 189 members states to tackle several crucial issues, namely ‘extreme poverty and hunger, universal primary education, gender equality and woman empowerment, child mortality, maternal health, HIV/AIDS, malaria and other diseases, environmental sustainability and globally developmental partnership’ (United Nations 2014). After 2015, the MDGs which was adopted by 189 members states was evaluated by comparing between the MDGs’ targets and its results. By using archival research data, this paper argues that the MDGs have not really failed in fighting against global poverty, because the MDGs showed a global willingness to alleviate numbers of poverty and the MDGs have achieved prominent improvement.